2021
DOI: 10.1108/itp-07-2020-0455
|View full text |Cite
|
Sign up to set email alerts
|

Is this real? Cocreation of value through authentic experiential augmented reality: the mediating effect of perceived ethics and customer engagement

Abstract: PurposeRapid advancements in augmented reality (AR) technology have created new opportunities for service providers and customers to cocreate value. Using AR as a platform for generating authentic experiences, the purpose of this study is to explore the impact of authentic experiences on customers' intention to cocreate value while considering the mediating influence of perceived ethics and customer engagement on this relationship.Design/methodology/approachAn online survey was used to collect data. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 128 publications
5
34
0
1
Order By: Relevance
“…In line with current research, we contend that AR is inherently suited for offering customers an authentic, vicarious examination of products online (Alimamy & Nadeem, 2021). Although AR supports various content formats (including visual cues, information layers, or face filters), most retail applications enable customers to interact with 3D product holograms within their immediate surroundings (Carrozzi et al, 2019)—which is forecasted to become the predominant mode of shopping online in the future (Deloitte, 2020).…”
Section: Conceptual Background and Hypothesessupporting
confidence: 75%
“…In line with current research, we contend that AR is inherently suited for offering customers an authentic, vicarious examination of products online (Alimamy & Nadeem, 2021). Although AR supports various content formats (including visual cues, information layers, or face filters), most retail applications enable customers to interact with 3D product holograms within their immediate surroundings (Carrozzi et al, 2019)—which is forecasted to become the predominant mode of shopping online in the future (Deloitte, 2020).…”
Section: Conceptual Background and Hypothesessupporting
confidence: 75%
“…This research confirmed that the stronger indicator for electronic word of mouth (e-WOM) happened when someone have good perceptions about ethical of using ride sharing application. Besides that, the research strengthens the finding by [2], [18], [20], in which an individual's relationship with ethical perceptions is significant in explaining value co-creation in using ride sharing application.…”
Section: Resultssupporting
confidence: 75%
“…Study on ethical perceptions as mediator between e-WOM and value co-creation is still very limited. Until now, ethical perceptions had been used as a mediator in study on relationship between consumer participation and value cocreation [2], relationship between social support and value co-creation [19] and relationship between authentic support and value co-creation [20]. In this study, we will show the influence of e-WOM on value co-creation with ethical perceptions as mediator.…”
Section: Ethical Perceptions As Mediator Between E-wom and Value Co-c...mentioning
confidence: 93%
“…Facilitating the cocreation of product and service experiences is a marketing priority, and reality‐enhancing technologies can support firms and consumers in this process by suggesting and transforming digital content against real or virtual world backgrounds (Alimamy & Nadeem, 2021; Boyd & Koles, 2019). For example, many garden design firms use AR apps (e.g., AR Landscaper, YARD) that allow consumers to interactively cocreate the design of their backyard.…”
Section: Balancing Value Cocreation and Privacy Concerns In Reality‐e...mentioning
confidence: 99%
“…At the same time, social media platforms utilize the technologies to facilitate communication between firms, consumers, and other consumers (e.g., Snapchat AR lenses). This offers new ways of cocreating value (Alimamy & Nadeem, 2021), while amplifying privacy concerns (Cowan et al, 2021). Furthermore, reality-enhancing technologies present unique opportunities as research tools that offer new insights into consumer behavior across marketing contexts (e.g., simulating new products in VR; Harz et al, 2021).…”
mentioning
confidence: 99%